Frequency dependency analysis for differential capacitive sensor - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azam, Amelia Wong (Universitas Ahmad Dahlan in collaboration with IAES Indonesia Section, 2019)
A differential capacitive sensing technique is discussed in this paper. The differential capacitive sensing circuit is making use of a single power supply. The design focus for this paper is on the excitation frequency dependency analysis to the circuit. Theory of the differential capacitive sensor under test is discussed and derivation is elaborated. Simulation results are shown and discussed. Next, results improvement has also been shown in this paper for comparison. Test was carried out using frequency from 40 kHz up to 400 kHz. Results have shown output voltage of Vout = 0.07927 Cx + 1.25205 and good linearity of R-squared value 0.99957 at 200 kHz. Potential application for this capacitive sensor is to be used for energy harvesting for its potential power supply.